(untitled) (Fractal: Journal of Psychology, 2009)
Recent data show that the female undewear industries in Franca/SP have presented considerable growth in that city which history has always been guided by the footwear industry. Due to the crisis in the footwear sector, especially intensified because of the competition with the industry in Asiatic countries, many major factories of shoes were closed, and with the exemption of labor, there was a process of reorganization of manufacturing structure, played in particular, by those who searched new insertion in the labor market. Facing this framework, a new vocation is born, basically controlled by women and creating jobs for other women - the underwear industry, which is growing sharply. We suppose that many of these women, ahead of today incipient industry of underwear, had some past experience in the shoe industries, which employ significant female workforce, mainly in the sectors of shavings and cutting of leather, painting and packaging, not counting the service of third sector where the presence of women is in any case, significant. We believe it because they are already in an economic-industrial environment related to fashion, so the transposition of the footwear to the underwear manufacturing, in spite of the obvious differences, represented for these women, a readjustment in their old skills used in the footwear industry. This paper ongoing, has the purpose of getting data about the history of this incipient industry, and through the report of these women know their trajectories of life and experiences they have brought to this new reality. It also intends to recognize which were the strategies they used to reorganize themselves in productive spaces, which are, in some cases their homes. In addition, it wants to know and identify other experiences that are articulated in the world of work.